ANALISIS SEMIOTIK WACANA IKLAN PROPERTI BERBAHASA INGGRIS DI SURAT KABAR DAN TELEVISI DI INDONESIA - Andriyanti, Erna; Mukminatun, Siti; Sudartinah, Titik (Kajian Linguistik dan Sastra, 2012)
This study is aimed at identifying facilities offered through English property advertisements in printed and electronic media in Indonesia, describing the meanings of lingual and non-lingual elements in the form of pictures in the advertisements and interpreting the messages based on sociocultural perspectives. This is a descriptive qualitative study, applying content analysis to 44 data taken from Kompas, The Jakarta Post, Trans TV and Metro TV. The results show as the following. There are 13 facilities offered through the advertisments. The dominating ones are service, recreation, furniture, and sports. The lingual elements exist in brand, slogan, and price. All brands and products symbolize grandeur, luxury, beauty, exclusiveness, and comfort in a modern life. Prices are in Rupiah, US and Singaporean Dollars, and Euro, indicating that the properties are marketed internationally. The visual elements, supporting the lingual meanings, consists of grand houses with gardens and swimming pools, luxurious furniture and interior designs and beaches. Based on sociocultural perspective, there is a cultural transfer of culture to a modern life-style. The use of English in the advertisements can be interpreted as a subtle way to sell the properties to foreign parties with big capital.